Edward Said and the religious effects of culture - Hart, William David (Cambridge studies in religion and critical thought ;, 2000)
This book provides a distinctive account of Edward Said's critique of modern culture by highlighting the religion-secularism distinction on which it is predicated. It refers to religious and secular traditions and to tropes that extend the meaning and reference of religion and secularism in indeterminate ways. It covers Said's heterogeneous corpus--from Joseph Conrad and the Fiction of Autobiography, his first book, to Orientalism, his most influential book, to his recent writings on the Palestinian question. The religion-secularism distinction lies behind Said's cultural criticism, and his notion of intellectual responsibility.